Hiding in plain sight? A review of post-convulsive leukocyte elevations - Vega, Jose L.; Komisaruk, Barry R.; Stewart, Mark (Frontiers in Neurology, 2022)
During physiological stress responses such as vigorous exercise, emotional states of fear and rage, and asphyxia, the nervous system induces a massive release of systemic catecholamines that prepares the body for survival by increasing cardiac output and redirecting blood flow from non-essential organs into the cardiopulmonary circulation. A curious byproduct of this vital response is a sudden, transient, and redistributive leukocytosis provoked mostly by the resultant shear forces exerted by rapid blood flow on marginated leukocytes. Generalized convulsive seizures, too, result in catecholamine surges accompanied by similar leukocytoses, the magnitude of which appears to be rooted in semiological factors such as convulsive duration and intensity. This manuscript reviews the history, kinetics, physiology, and clinical significance of post-convulsive leukocyte elevations and discusses their clinical utility, including a proposed role in the scientific investigation of sudden unexpected death in epilepsy (SUDEP).